Macrophages Interaction and MicroRNA Interplay in the Modulation of Cancer Development and Metastasis - Iurca, Ioana; Tirpe, Alexandru; Zimta, Alina-Andreea; Moldovan, Cristian; Gulei, Diana; Slabý, Ondřej; Condorelli, Gerolama; Berindan-Neagoe, Ioana (Frontiers in Immunology, 2020)
Advancement in cancer research has shown that the tumor microenvironment plays a crucial role in the installation, progression, and dissemination of cancer cells. Among the heterogeneous panel of cells within the malignant microenvironment are tumor-associated macrophages that are sustaining the malignant cells through strict feedback mechanisms and spatial distribution. Considering that the presence of metastasis is one of the main feature associated with decreased survival rates among patients, in the present article we briefly present the involvement of tumor-associated macrophages in the hallmarks of metastasis and their microRNA-related regulation with a focus on lung cancer in order to coordinate the vast information under one pathology. As shown, these cells have emerged as coordinators of immunosuppression, angiogenesis and lymphangiogenesis, vessel intravasation and extravasation of cancer cells, and premetastatic niche formation, transforming the macrophages in potential therapeutic targets and also prognostic markers according to their density within the tumor and polarization phenotype. An indirect therapeutic approach on tumor-associated macrophages can be also represented by regulation of microRNAs involved in their polarization and implicit oncogenic features. Examples of these microRNAs consist in the highly studied miR-21 and miR-155, but also other microRNA with less feedback in the literature: miR-1207-5p, miR-193b, miR-320a, and others.